Hubungan Penerapan Model Reguler Pendidikan Kepramukaan dengan Hasil Belajar Kognitif Siswa SD: Hubungan Penerapan Model Reguler Pendidikan Kepramukaan dengan Hasil Belajar Kognitif Siswa SD - Noti Ashar; Lukman; Nani Yuliantini (JURIDIKDAS, 2023)
This study aims to determine the relationship of applying the regular model of scouting education (x) with students' cognitive learning outcomes (y) at sd negeri 01 kota bengkulu. This type of research is quantitative research. The population of this study amounted to 41 student scout members who followed the regular model of sampling total sampling technique. Data collection techniques used questionnaires, recapitulation of weekly repeat values ​​in cognitive and documentation aspects. Research instruments were tested using validity and reliability. While prerequisite analysis test using normality test, homogeneity test, and hypothesis test. Data analysis technique is done by using "product moment correlation" formula. This technique is used to determine the significance of independent variable relation and dependent variable by rhitung count with rtabel with 5% significant level. Based on the results of data analysis diproleh value rhitung = > 0.698 rtabel = 0.308 which means there is a relationship of the regular modeling modeling of scouting education with students' cognitive learning outcomes with very strong interpretation. Furthermore, from the significance test results obtained t count 6.087 ≥ ttabel = 1.664 which means there is a significant relationship between variables, with a contribution of 48.72% between the application of regular model of scouting education with cognitive learning outcomes of elementary school students 01 kota bengkulu. Based on this, it can be concluded that ha accepted, where there is a relationship of application of regular model of scouting education with cognitive learning outcomes at state elementary school 01 kota Bengkulu.